«The School, where Eastern Languages Will Be Taught Widely»: The History of the Lazarev Institute in the First Half of the XIX Century in the Context of the Policy of the Russian Empire in the Caucasus - M. A. Volhonsky (Международная аналитика)
The article highlights the history of creation and transformation of the Lazarev Institute in the first half of the nineteenth century. It was founded in Moscow in 1815 thanks to the family of rich Armenian industrialists as a private institution and underwent a complex evolutionary path from school for children from poor Armenian families to the Institute, one of the recognized in Russia centers for learning oriental languages. A key role in the history of the Lazarev Institute played two factors: energetic cultural and educational activities of Lazarev family, as well as the interest of the government of the Russian Empire in preparation for the Caucasian administration of interpreters and officials with knowledge of oriental languages.